Selective Uptake of Carboxylated Multi-Walled Carbon Nanotubes by Class A Type 1 Scavenger Receptors and Impaired Phagocytosis in Alveolar Macrophages - Ruhung Wang; Rishabh Lohray; Erik Chow; Pratima Gangupantula; Loren Smith; Rockford Draper (Nanomaterials, 2020)
The production and applications of multi-walled carbon nanotubes (MWNTs) have increased despite evidence that MWNTs can be toxic. Recently, we reported that the binding of Pluronic® F-108 (PF108)-coated carboxylated MWNTs (C-MWNTs) to macrophages is inhibited by class A scavenger receptors (SR-As) antagonists (R. Wang et al., 2018. Nanotoxicology 12:677–690). The current study investigates the uptake of PF108-coated MWNTs by macrophages lacking SR-A1 and by CHO cells that ectopically express SR-A1. Macrophages without SR-A1 failed to take up C-MWNTs and CHO cells that expressed SR-A1 did take up C-MWNTs, but not pristine MWNTs (P-MWNTs) or amino-functionalized MWNTs (N-MWNTs). The dependence of C-MWNT uptake on SR-A1 is strong evidence that SR-A1 is a receptor for C-MWNTs. The consequences of SR-A1-dependent C-MWNT accumulation on cell viability and phagocytic activity in macrophages were also studied. C-MWNTs were more toxic than P-MWNTs and N-MWNTs in cell proliferation and colony formation tests. C-MWNTs reduced surface SR-A1 levels in RAW 264.7 cells and impaired phagocytic uptake of three known SR-A1 ligands, polystyrene beads, heat-killed E. coli, and oxLDL. Altogether, results of this study confirmed that SR-A1 receptors are important for the selective uptake of PF108-coated C-MWNTs and that accumulation of the C-MWNTs impairs phagocytic activity and cell viability in macrophages.